Complications during mechanical ventilation—A pediatric intensive care perspective - Sood, Shawn; Ganatra, Hammad A.; Perez Marques, Francesca; Langner, Travis R. (Frontiers in Medicine, 2023)
Mechanical ventilation is a common procedure performed in pediatric intensive care units, with over 20% of patients requiring invasive ventilator support. The most common indication for endotracheal intubation and ventilation in the pediatric population is respiratory failure either due to respiratory embarrassment or neurologic pathology. Despite the use of ventilation modes that are lung protective in the pediatric population, complications of mechanical ventilation occur frequently. These include atelectasis, post-extubation stridor, perioral tissue damage, ventilator associated pneumonia, mucus plugging, pneumothorax, pneumomediastinum, and ICU neuromyopathy. The purpose of this review is to discuss the risk factors, presentation and management of complications associated with mechanical ventilation in the pediatric population.